PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI KANTOR KPU KABUPATEN TANAH DATAR - Amrullah Amrullah; Susi Evanita (Jurnal Riset Manajemen Bisnis dan Publik, 2014)
The aim of this research is to describe the influence of reward toward working motivation of the civil servant at KPU (Election Commission) in Tanah Datar regency, and the influence of reward and working motivation toward working satisfactory of the civil servant at KPU in Tanah Datar regency. Population of this research are all of the civil servants at KPU in Tanah Datar regency.  There are 55 person.  Sample of this research were taken by using Proportional Cluster Random Sampling.  The researcher took 49 person. Data were analyzed by using Line Analysis and supported by SPSS program (Statistical Package for Social Sciences).  The result of this research shows that: 1) reward has significant influence toward working motivation of the civil servants at KPU in Tanah Datar regency, and 2) reward and working motivation have significant influence toward working satisfactory of the civil servants at KPU in Tanah Datar regency.  It is suggested to the leader of KPU in Tanah Datar regency to be able to manage  as well as possible the system of distributing rewards, giving respectation orally or written to the civil servant who has good reputation in their work, giving reward to the civil servant who has good reputation in their work, giving extra income to the civil servant along their work.  Furthermore, the leader is also expected to be always motivating their staff to be diligent in working, to be serious in giving motivation in working.  This way can be apllied by giving reward and punishment toward the civil servants.